Differential Expression of ABC Transporter Genes in Brain Vessels vs. Peripheral Tissues and Vessels from Human, Mouse and Rat - Wandong Zhang; Qing Yan Liu; Arsalan S. Haqqani; Ziying Liu; Caroline Sodja; Sonia Leclerc; Ewa Baumann; Christie E. Delaney; Eric Brunette; Danica B. Stanimirovic (MDPI AG, 2023)
Background: ATP-binding cassette (ABC) transporters comprise a superfamily of genes encoding membrane proteins with nucleotide-binding domains (NBD). These transporters, including drug efflux across the blood-brain barrier (BBB), carry a variety of substrates through plasma membranes against substrate gradients, fueled by hydrolyzing ATP. The expression patterns/enrichment of ABC transporter genes in brain microvessels compared to peripheral vessels and tissues are largely uncharacterized. Methods: In this study, the expression patterns of ABC transporter genes in brain microvessels, peripheral tissues (lung, liver and spleen) and lung vessels were investigated using RNA-seq and WesTM analyses in three species: human, mouse and rat. Results: The study demonstrated that ABC drug efflux transporter genes (including ABCB1, ABCG2, ABCC4 and ABCC5) were highly expressed in isolated brain microvessels in all three species studied; the expression of ABCB1, ABCG2, ABCC1, ABCC4 and ABCC5 was generally higher in rodent brain microvessels compared to those of humans. In contrast, ABCC2 and ABCC3 expression was low in brain microvessels, but high in rodent liver and lung vessels. Overall, most ABC transporters (with the exception of drug efflux transporters) were enriched in peripheral tissues compared to brain microvessels in humans, while in rodent species, additional ABC transporters were found to be enriched in brain microvessels. Conclusions: This study furthers the understanding of species similarities and differences in the expression patterns of ABC transporter genes; this is important for translational studies in drug development. In particular, CNS drug delivery and toxicity may vary among species depending on their unique profiles of ABC transporter expression in brain microvessels and BBB.